Analysis of hemodynamic parameters and quality of life in patients with chronic kidney disease and arterial hypertension - Khokonova , Tamara Muratovna; Sizhazheva , Sofiat Khasenovna; Sabanchieva , Zhaneta Huseynovna; Nalchikova , Marina Tembulatovna; Elmurzayeva , Jannet Anvarovna; Urusbieva , Dzhanneta Magometovna; Khakuasheva , Inara Aslanovna; Solyanik , Svetlana Sergeevna (Journal of the University of Zulia, 2021)
Purpose. The work is devoted to study the effects of antihypertensive, lipid-lowering and metabolic therapy in office and the average hemodynamic parameters, the parameters of central pressure in the aorta, vascular wall stiffness and quality of life in patients with CKD stage 3 in combination with arterial hypertension of 1-2 degrees, and without it. Materials and methods. Were examined patients with arterial hypertension of 1-2 degrees and CKD stage 3. Measured hemodynamic parameters with the help of a daily BP monitor “BPLab”. The quality of life of patients was assessed by the questionnaire MOS SF36. Results. The greatest changes in the indicators of central hemodynamics and vascular stiffness were noted in the group of patients with comorbidity. Conclusion. The combination of antihypertensive therapy (losartan and diltiazem) with meldonium and rosuvastatin significantly decreases indices of central and peripheral hemodynamics and vascular stiffness. Add meldonium part of therapy significantly improves the quality of life of patients.